2011
DOI: 10.1021/jp203202e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Strategies in the HDV Ribozyme: Chelated and Diffuse Metal Ion Interactions and Active Site Protonation

Abstract: The crystal structure of the precleaved form of the hepatitis delta virus (HDV) ribozyme reveals two G•U wobbles near the active site: a rare reverse G•U wobble involving a syn G base, and a standard G•U wobble at the cleavage site. The catalytic mechanism for this ribozyme has been proposed to involve a Mg2+ ion bound to the reverse G•U wobble, as well as a protonated C75 base. We carried out molecular dynamics simulations to analyze metal ion interaction with the reverse and standard G•U wobbles and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(109 citation statements)
references
References 52 publications
4
105
0
Order By: Relevance
“…Steady-state and time-resolved FRET measurements consistently detected an ∼8-Å lengthening of the end-to-end distance along the P2-P4 axis accompanying cleavage in solution, an elongation consistent with the range previously found for trans-and cis-acting HDV ribozymes Tanaka et al 2002;Jeong et al 2003;Harris et al 2004). We also performed a total of 1.8 µsec of MD simulations that showed that the hammerhead ribozyme model of the substrate conformation in the active site is compatible with a favorable catalytic in-line fitness (a measure of the poise to undergo catalytic transesterification), as long as C75 is protonated, consistent with previous results (Veeraraghavan et al 2011). In contrast, intermolecular crystal contacts and 2 ′ -deoxyribose modifications found in the crystal structure near the active site result in unfavorable in-line fitness, offering an explanation for the lack of experimental electron density in this region.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Steady-state and time-resolved FRET measurements consistently detected an ∼8-Å lengthening of the end-to-end distance along the P2-P4 axis accompanying cleavage in solution, an elongation consistent with the range previously found for trans-and cis-acting HDV ribozymes Tanaka et al 2002;Jeong et al 2003;Harris et al 2004). We also performed a total of 1.8 µsec of MD simulations that showed that the hammerhead ribozyme model of the substrate conformation in the active site is compatible with a favorable catalytic in-line fitness (a measure of the poise to undergo catalytic transesterification), as long as C75 is protonated, consistent with previous results (Veeraraghavan et al 2011). In contrast, intermolecular crystal contacts and 2 ′ -deoxyribose modifications found in the crystal structure near the active site result in unfavorable in-line fitness, offering an explanation for the lack of experimental electron density in this region.…”
Section: Introductionsupporting
confidence: 88%
“…Previous MD studies have identified two protonated cytosines as structurally important: C41, that upon protonation forms a rare stabilizing quadruple interaction just below the active site (Krasovska et al 2005;Veeraraghavan et al 2010), and C75, that upon protonation promotes a stable active site in the context of the trans-acting precursor (Veeraraghavan et al 2011) as well as cis-acting product structure (Krasovska et al 2005). Protonation in the context of the new, trans-acting ribozyme is justified since the crystal structure was obtained at a pH of 5.0 (Chen et al 2010); however, since the pK a of C75 of the HDV ribozyme was measured as ∼6.4 (Nakano et al 2000;Gong et al 2007), at the more physiological pH of 7.5 used in our solution, probing a protonated C75H…”
Section: (B)mentioning
confidence: 99%
“…The U c -G g NOE cross peak is in a position that is typical for a G·U wobble pair. As the formation of an extra G·U wobble at the base of the P3 helix has been suggested for the HDV ribozyme (Krasovska et al 2006;Chen et al 2010;Veeraraghavan et al 2011;Kapral et al 2014), we speculated that the corresponding G25·U20 wobble forms as well in the CPEB3 ribozyme upon addition of Mg 2+ , giving rise to the observed NOE correlation. The hypothesis was both tempting and probable, however it longed for more substantial evidence, since theoretically, also other scenarios might have been occurring, such as, e.g., the formation of a G19·U26 wobble.…”
Section: Locating Mg 2+ Binding Sites By Nmr Spectroscopymentioning
confidence: 76%
“…Also, the outer-sphere binding site at the G1·U36 wobble (khaki nucleotides in Fig. 8C) (G1-U37 in HDV) occurs in both ribozymes and has been suggested to stabilize the P1.1 minihelix (Veeraraghavan et al 2011), which maintains stacking interactions with P1. Probably, there are further binding sites for Mg 2+ in the core region of the CPEB3 ribozyme (orange and green-blue nucleotides in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation